2021
DOI: 10.1002/essoar.10508890.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health and Safety Effects of Airborne Soil Dust in the Americas and Beyond

Abstract: Risks associated with dust hazards are often underappreciated, a gap between the knowledge pool and public awareness that can be costly for impacted communities. This study reviews the emission sources and chemical, physical, and biological characteristics of airborne soil particles (dust) and their effects on human and environmental health and safety in the Pan-American region. American dust originates from both local sources (western United States, northern Mexico, Peru, Bolivia, Chile, and Argentina) and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 505 publications
0
5
0
Order By: Relevance
“…In the northern Chihuahuan Desert, our simulated pattern of large dust emission fluxes from unvegetated and poorly vegetated regions including dry playas is also consistent with previous studies (Baddock et al., 2011; Hennen et al., 2022). The large dust emitting regions in the simulations covering the southwestern Colorado Plateau and northern Chihuahuan Desert also correspond to regions of measured large spring season sediment flux (Bergametti & Gillette, 2010), dust emission hotspots that contribute to blowing dust on highways (Tong et al., 2023) and large PM concentration (Hand et al., 2017). In the southwestern Colorado Plateau and northern Chihuahuan Desert, fine dust (PM 2.5 ) concentration peaks (1.7–2.22 μgm −3 ) are observed during the spring season (Hand et al., 2017).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the northern Chihuahuan Desert, our simulated pattern of large dust emission fluxes from unvegetated and poorly vegetated regions including dry playas is also consistent with previous studies (Baddock et al., 2011; Hennen et al., 2022). The large dust emitting regions in the simulations covering the southwestern Colorado Plateau and northern Chihuahuan Desert also correspond to regions of measured large spring season sediment flux (Bergametti & Gillette, 2010), dust emission hotspots that contribute to blowing dust on highways (Tong et al., 2023) and large PM concentration (Hand et al., 2017). In the southwestern Colorado Plateau and northern Chihuahuan Desert, fine dust (PM 2.5 ) concentration peaks (1.7–2.22 μgm −3 ) are observed during the spring season (Hand et al., 2017).…”
Section: Discussionmentioning
confidence: 56%
“…In spring (March–May), dust events across the Southwestern United States (hereafter Southwest) bring deleterious impacts on human health by degrading air quality (Achakulwisut et al., 2017; Hand et al., 2017, 2019); regional transportation by reducing visibility (Tong et al., 2023); ecosystem services and agricultural production by losing topsoil and associated nutrients and soil carbon (Duniway et al., 2019; Webb et al., 2017); and water resources by impacting dust radiative forcing of snow melt (Rahimi et al., 2020; Skiles & Painter, 2017). Dust transported from regionally active source areas affects mountain snowpack in the Upper Colorado River Basin (Skiles et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wind erosion and resultant blowing dust are important threats to ecosystems and human health in the Chihuahuan Desert of New Mexico (Figure 4). Wind erosion selectively removes fine soil, nutrients, and carbon (Webb et al., 2012), while blowing dust exposure is linked to adverse health effects such as asthma, Valley fever infections, and is a safety hazard to road transportation (Tong et al., 2023). Ecologically, the region is dominated by grasslands and savannas, which have experienced extensive shrub encroachment and loss of perennial grasses that are desirable for livestock production (Bestelmeyer et al., 2018).…”
Section: Case Study: Assessing Wind Erosion Risk In the Chihuahuan De...mentioning
confidence: 99%
“…These dust events have an important effect on the atmospheric system, influencing radiation (Lau et al., 2020), cloud formation (Chen et al., 2019), and the atmospheric vertical electric field (Ardon‐Dryer, Chmielewski, et al., 2022). Air quality, human well‐being, and human health are also affected, mainly negatively (Ardon‐Dryer & Kelley, 2022; Tong et al., 2023a, 2023b). Dust in North America is estimated to contribute ∼2.5% (0.3–0.9 Tg) of the global dust loading for particles with diameters up to 20 μm (PM 20 ) (Kok et al., 2021), yet some studies estimated much higher concentrations as found by Urban et al.…”
Section: Introductionmentioning
confidence: 99%